Extracellular Lipase from Pseudomonas aeruginosa SB-37: Production by Solid State Fermentation, Immobilization, and Characterization - Haryati, Titin; Haryono, Norman Yoshi; Nugraheni, Dian; Fatmawati, Fenti; Dewi, Alfina Kusuma; Syach, Muhammad Zahran Edlian (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Native lipase is still promising as an industrial biocatalyst. This study aimed to investigate the production of native local lipase using solid state fermentation (SSF) methods, immobilization the lipase by Ca-alginate entrapment, and characterization based on substrate preferences. To obtain high lipase production using SSF methods, we optimized the type of agro-wastes substrates, fermentation time, oil induction percentage and volume of preculture percentage. The optimal condition for lipase production via solid-state fermentation involved a 7% (v/v) preculture of Pseudomonas aeruginosa SB-37, utilizing palm kernel meal as the substrate, supplemented with 6% (v/w) oil induction (soybean oil:tween 80 = 75:25) at 50 °C for 24 h. This gave a lypolitic activity value of 2 U/gds (gram dry weight substrates). Since the protein profile of extracellular lipase has a few protein bands, we perform direct immobilization on crude protein supernatant. Immobilization by Ca-alginate entrapment results in loading capacity and recovery activity values of 86.84% and 148%, respectively. The immobilized lipase retained 92% activity until four batch repetition and keep 40% activity at tenth batch. The highest hydrolytic activity of immobilized lipase was 0.9 U/g gel on the pNP_8 substrates. While the highest transesterification activity was observed with acetonitrile solvent and substrates of pNP_8 and isopropanol with the activity value at 0.6 U/g gel. This present study emphasized the feasibility of producing lipase as a biocatalysts using economical agro-industrial wastes and efficient immobilization using entrapment method. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).